Comparative Population Genomics and Biophysical Modeling of Shrimp Migration in the Gulf of Mexico Reveals Current-Mediated Connectivity - Timm, Laura E.; Isma, Lys M.; Johnston, Matthew W.; Bracken-Grissom, Heather D. (Frontiers in Marine Science, 2020)
The Gulf of Mexico experiences frequent perturbations, both natural and anthropogenic. To better understand the impacts of these events, we must inventory natural variability within the ecosystem, communities, species, and populations, and contextualize these findings in relation to physical features. Here, we present an integrated study of comparative population genomics and biophysical oceanography. Targeting three species of mesopelagic shrimp common to the Gulf of Mexico midwater (Acanthephyra purpurea, Systellaspis debilis, and Robustosergia robusta), we analyzed genetic diversity and population connectivity as proxies for species health and resilience, respectively. We also simulated a range of vertical migratory behaviors of the shrimp to infer the relationship between diel vertical migration and horizontal transmission between the Gulf of Mexico and the greater Atlantic Ocean. This study aims to establish biological baselines and characterize these values in terms of the prevailing oceanographic feature of the midwater: the Gulf Loop Current. Generally, the oplophorid species (A. purpurea and S. debilis) exhibit lower genetic diversity and higher interpopulation homogeneity compared to the sergestid (R. robusta). Biophysical simulations suggest the differences in vertical migratory regimes between these two groups have important implications for horizontal transport out of the Gulf of Mexico. Because of the difference in vertical migration patterns, access to the Gulf Loop Current varies across taxa and impacts inter-basin migration. Our findings suggest a negative correlation between surface abundance and genetic diversity in these three shrimp species. We hypothesize that this correlation may be due to the relationships between surface abundance and access to the fastest moving waters of the Gulf Loop Current.